Multifunctional benzoin derivatives based macrophotoinitiators: Synthesis, inorganic fillers modification, and fabrication of composite materials. Issue 26 (23rd April 2022) - Ohar, Halyna; Tokareva, Maria; Nagursky, Oleg; Mosnáček, Jaroslav; Tokarev, Viktor
Abstract: Photopolymer composites are the materials with wide application potential in paints and varnishes, diverse lithographic processes, electronics, medicine, and so forth. Here a new approach to the synthesis of macrophotoinitiators (MPIs) were developed and their effective application for curing polymer composites after immobilization on the surface of diverse mineral fillers was demonstrated. The MPIs were synthesized by reaction of benzoin or 3‐hydroxy‐1, 2‐diphenyl‐2‐(propan‐2‐yloxy)propan‐1‐one as a photodissociating species with a copolymer of maleic anhydride with methyl methacrylate as carrier. Chemical structure of MPIs and the content of the tethered photoinitiating moieties were determined using 1 NMR‐, IR‐, and UV‐spectroscopies. Photolysis of MPIs was investigated in details using a spot‐light curing system. It was demonstrated that MPIs are effective surface modifiers of mineral fillers, such as titanium dioxide, zinc oxide, and nanohydroxyapatite; and behave as effective photoinitiators. The benefits of using the fillers surface‐modified by MPIs in photo‐curable polymer composites were discussed. Abstract :